Single‐Cell Detection and Photostimulation on a Microfluidic Chip Aided with Gold Nanorods - Zhu, Yujie; Xu, Hui; Wei, Xunbin; He, Hao (Cytometry. Part A, 2020)
Gold nanorods (GNRs) can be easily designed and synthesized to respond to photons in the near infrared (NIR) band. The photostimulation by laser irradiation can be mediated and enhanced by GNRs to introduce localized damage to cells for photodynamic/photothermal therapy (PDT or PTT). In this study, we show that cells stained with GNRs can be detected and stimulated simultaneously by short flashes of femtosecond‐laser irradiation on a microfluidic system effectively. In the relatively high‐throughput cell flow, the two‐photon luminescence from GNRs can be excited and detected. The GNRs also mediate and enhance the transient photostimulation of the cells. After photostimulation, cells can remain alive, go to apoptosis, or necrosis, respectively. The stimulation effect is strongly dependent on the photon density and stimulation duration. We found the cells remain alive, go to apoptosis or necrosis, dependent on the GNR staining, the laser illumination pattern and duration. Hence, our system provides a simple and effective method for high‐throughput cell stimulation and analysis on chip. © 2019 International Society for Advancement of Cytometry